18 Efficacy of maintenance olaparib plus bevacizumab by biomarker status in clinical higher- and lower-risk patients with newly diagnosed, advanced ovarian cancer in the PAOLA-1 trial. (13th November 2020) - Harter, P; Petran, D; Scambia, G; Ortega, E; Tsibulak, I; Nagao, S; Vergote, I; Meunier, J; Priou, F; Sverdlin, R; Milenkova, T; Ray-Coquard, I; et al.
Abstract : Introduction: In the Phase III PAOLA-1/ENGOT-ov25 trial (NCT02477644 ), adding maintenance olaparib to bevacizumab improved progression-free survival (PFS) in patients with advanced ovarian cancer in response after first-line platinum-based chemotherapy plus bevacizumab (HR 0.59; 95% CI 0.49–0.72) (Ray-Coquard et al. NEJM 2019). Outcomes in patients classified by clinical risk according to biomarker status are unknown. Methods: Patients were classified as higher-risk (stage III patients with upfront surgery and residual disease or who received neoadjuvant chemotherapy, or stage IV patients) or lower-risk (stage III patients with upfront surgery and no residual disease). This exploratory analysis evaluated PFS in higher-risk and lower-risk patients, including by biomarker status: homologous recombination deficiency (HRD)-positive, HRD-negative/unknown and tumour BRCA mutation (BRCAm)-positive. Results: Of 806 randomized patients, 74% were higher risk and 26% were lower risk, with median follow-up of 22.4 and 23.8 months, respectively. PFS significantly favoured olaparib plus bevacizumab versus placebo plus bevacizumab in higher-risk and lower-risk patients. In both higher- and lower-risk patients, the greatest PFS benefit was seen with olaparib plus bevacizumab versus bevacizumab alone in the HRD-positive subgroup (figures 1 and 2) and the subgroup with a tumour BRCAm (figure 2 ). Outcomes in the higher- and lower-risk HRD-negative/unknown subgroups are shown in figure 2 . Conclusions: In PAOLA-1, maintenance olaparib plus bevacizumab provided a substantial PFS benefit over bevacizumab alone in higher-risk and lower-risk patients, especially in the HRD-positive and BRCAm populations.